Reflexiones sobre la práctica docente en la implementación de estrategias metacognitivas en producciones escritas con estudiantes de grado quinto (2017)
The present study arose from a need that we observe like Spanish teachers in our classroom. The students were presenting difficulties of capturing the ideas of structured and assertive form in a certain communicative situation. Fruit of our reflections, we understood that the orientation in the process of education and learning of the writing was not the most suitable. The written production was a product of the immediateness and we were not giving him the importance that it has in the academic, personal and social life. On this matter, we realize this study based on the critical paradigm, under the Investigation methodology Action, with the main target to implement new strategies in the classroom, which they were leading to the achievement of more conscious and assertive written productions in the fifth grade students I conscript of primary. But principally, we look for the comprehension and the improvement of our teaching practice...